Phylogenetic relationship among potential citrus rootstock species based on seed characteristics and germination metrics - RYMBAI, HEIPLANMI; TALANG, HAMMYLLIENDE; JHA, ANJANI KUMAR; VERMA, VEERENDRA KUMAR; MAWLEIN, JOIEDEVIVRESON; DEVI, MAYANGLAMBAM BILASHINI (The Indian Journal of Agricultural Sciences, 2025)
Wild citrus species could be utilised as potential rootstocks in the citriculture industry. Seed germination, seedling characteristics, and their metrics are important traits of rootstocks and their evolutionary relationships. However, the limited information available affects the propagation and field performance of citrus. The experiment was conducted during winter (rabi) season of 2022 to 2024 at ICAR-Research Complex for NEH Region, Umiam, Meghalaya to understand the germination, growth behaviours and phylogenetic relationship of citrus rootstock species. Fifteen potential citrus rootstocks selected for the study were Citrus maxima, C. jambhiri, C. karna, C. latipes, C. limonia, C. aurantifolia, C. limon, C. macroptera, C. medica, C. paradisi, C. reshni, C. trifoliata, C. taiwanica, C. volkameriana, and C. indica. Results showed that the maximum germination traits, seedling growth and their metrics were obtained in C. jambhiri, C. latipes, C. limonia, C. maxima, and C. volkameriana. The highest chlorophyll index was recorded in C. limon (80.8 ± 3.7) and C. medica. Germination was strongly correlated with the germination speed index (r = 0.746**), mean daily germination (r = 0.845**), peak (r = 0.512**), and germination value (r = 0.596**). Principal component analysis revealed the presence of a wider variability for germination and seedling traits, with the first five components (eigen value>1) contributing 78.69% of the total variation. Phylogenetic analysis revealed that cluster I was monogenotypic (C. trifoliata) and cluster II comprised commonly used rootstocks, indicating a close relationship between them. Therefore, C. jambhiri, C. limonia, C. maxima, and C. latipes exhibited higher performance in germination behaviours, growth, and vigour of seedlings. Germination percentage and germination metrics could be important selection criteria for the improvement and utilisation of these species in propagation.